Metformin Does Not Inhibit Exercise-Induced Lipolysis in Adipose Tissue in Young Healthy Lean Men - Krauzová, Eva; Tůma, Petr; de Glisezinski, Isabelle; Štich, Vladimír; Šiklová, Michaela (Frontiers in Physiology, 2018)
Objective: Metformin was shown to exert an antilipolytic action in adipose tissue (AT) that might mediate beneficial effects on lipid metabolism in diabetic patients. However, during exercise, the inhibition of induced lipolysis in AT would limit the energy substrate supply for working muscle. Thus, the aim of this study was to investigate whether metformin exerts inhibitory effect on exercise-induced lipolysis in subcutaneous adipose tissue (Moro et al.) in humans. Approach: Ten healthy lean men underwent two exercise sessions consisting of 60 minutes of cycling on bicycle ergometer combined with a) orally administered metformin and b) metformin locally administered into SCAT. Microdialysis was used to assess lipolysis in situ in SCAT. Glycerol, metformin and lactate, were measured in dialysate and plasma by enzyme colorimetric kits and capillary electrophoresis. Results: Metformin levels increased continuously in plasma during 3 hours after oral administration, and peaked after 3.5h (peak concentration 4ug/ml). Metformin was detected in dialysate outflowing from SCAT and showed a similar time-course as that in plasma with the peak concentration of 1,3 ug/ml. Metformin was detected in dialysate outflowing from SCAT and showed a similar time-course as that in plasma with the peak concentration of 1,3 ug/ml. The lipolytic rate in SCAT (assessed as glycerol release) increased in response to exercise (4.3 ± 0.5 fold vs. basal; p = 0.002) and was not suppressed either by local or oral metformin administration. The lactate levels increased in plasma and in dialysate from SCAT after 30 – 60 min of exercise (3.6 fold vs. basal; p = 0.015; 2.75 fold vs. basal; p = 0.002, respectively). No effect of metformin on lactate levels in SCAT dialysate or in plasma during exercise was observed. Conclusions: Metformin did not reduce the exercise-induced lipolysis in SCAT. This suggests that metformin administration does not interfere with the lipid mobilization and energy substrate provision during physical activity.